PENGARUH PENDIDIKAN, SIKAP KERJA, DAN KETERAMPILAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA LPP-RRI MATARAM (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of education variables, work attitudes, and work skills on the work performance of LPP-RRI Mataram employees. This research is an associative research with data collection techniques of observation, interviews and questionnaires. The data analysis technique used is the measurement scale, instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination (R2) using SPSS version 26. The results of this study indicate that the education variable (X1) has a significant effect on employee performance with a t-count value of 2.954 > from t-table 1.998 with a significant value of 0.004. Work attitude (X2) has no effect on employee performance with a t-count value of 1.058 < from t-table 1.998 with a significant value of 0.294. Work skills (X3) have a significant effect on employee performance with a t value of 4.408 > from t table 1.998 with a significant value of 0.000. Simultaneously, all independent variables (education, work attitudes, and work skills) together have a significant effect on employee work performance with a calculated F value of 25.688 and a significance level of 0.000 less than 0.05.